TINJAUAN TAFSIR AHKAM TENTANG PARIWISATA SYARIAH - Lina Pusvisasari (Prodi Hukum Keluarga Islam (Ahwal Asy-Syakhsiyyah) Fakultas Syariah Unisba, 2020)
ABSTRACTThe world of tourism today is very sad due to its negative impacts, such as promiscuity, alcoholism, drug trafficking, and so on. Tourism observers continue to make inroads, so that the development of tourism in Indonesia can have a positive impact on people's lives. including developing a type of halal tourism or sharia tourism. The purpose of this study provides an overview of the Al-Quran and Sunnah about tourism based on sharia principles, both related to recommendations, goals, ethics, basic principles of Islam and management of Islamic tourism so that in the future sharia tourism will become part of the mental and spiritual education process of the Muslim community. The method used in this study is a normative qualitative method which is a study to solve a problem that basically relies on critical and in-depth review of relevant library materials. The results of this study are also expected to make a positive contribution to the government in this case the Ministry of Tourism and Culture both at the district / city, provincial and national levels in order to develop sharia tourism in Indonesia. Keywords: al-Quran, al-Sunnah, Tourism.